Теоретичні аспекти визначення адміністративної діяльності органів та установ Державної кримінально-виконавчої служби України - Пузирний, В. Ф.; Пузырный, В. Ф.; Puzyrnyj, V. (Одеса : Юрид. л-ра, 2014)
In the article the conducted development of theoretical aspects of determination of administrative activity of organs and establishments of Government criminally-executive service of Ukraine. The different scientific looks researched for formulation of concept of administrative activity, the basic constituents of this concept are certain in relation to penitentiary organs and establishments
Пузирний В. Ф. Теоретичні аспекти визначення адміністративної діяльності органів та установ Державної кримінально-виконавчої служби України / В. Ф. Пузирний // Актуальні проблеми держави і права: зб. наук.пр. /редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.]; МОН України, НУ ОЮА. – Одеса: Юрид. л-ра, 2014. – Вип. 71. - С. 61-67.
Keywords: адміністративна діяльність; управління; органи виконання покарань; установи виконання покарань; административная деятельность; управление; органы исполнения наказаний; учреждения исполнения наказаний; administrative activity; management; organs of execution of punishments; establishment of execution of punishments